2011
DOI: 10.2139/ssrn.1896516
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of College Major Choice: Identification Using an Information Experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
314
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(336 citation statements)
references
References 47 publications
19
314
2
1
Order By: Relevance
“…As advocated in previous studies (e.g. Blass et al 2010;Stinebrickner and Stinebrickner 2014b;Wiswall and Zafar 2015a), we also allow students to express uncertainty about their future choices by asking them to state how likely they believe it is that they will continue in full-time education, on a 0-100% scale. Given that students may be subject to different shocks that may not yet have been realized at the time of the survey, it is important to allow students to express this uncertainty.…”
Section: Elicitation Of Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…As advocated in previous studies (e.g. Blass et al 2010;Stinebrickner and Stinebrickner 2014b;Wiswall and Zafar 2015a), we also allow students to express uncertainty about their future choices by asking them to state how likely they believe it is that they will continue in full-time education, on a 0-100% scale. Given that students may be subject to different shocks that may not yet have been realized at the time of the survey, it is important to allow students to express this uncertainty.…”
Section: Elicitation Of Beliefsmentioning
confidence: 99%
“…Second, our study relates to the literature that investigates how beliefs about pecuniary and non-pecuniary benefits affect students' choice of major (Zafar 2013;Wiswall and Zafar 2015a, 2018, 6 high-school track (Giustinelli 2016), and which specific university to attend (Delavande and Zafar 2019). In contrast to these studies, our analysis focuses on students' decisions to continue in further education (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Dominitz and Manski sequentially elicited 13. These include Arcidiacono et al (2012), Giustinelli (forthcoming), Stinebrickner (2012, 2014), Wiswall andZafar (2015a, 2015b), and Zafar (2011and Zafar ( , 2013, some of which we describe further below.…”
Section: A Assumptions Versus Measurement Of Subjective Expectationsmentioning
confidence: 99%
“…He uses the data to study gender differences in observed college major choices and expectations formation by students. In a follow-up study with NYU students, Wiswall andZafar (2015a, 2015b) also analyze college major choice and formation of students' expectations about their college major choice In studies concerned with schooling expectations, Stinebrickner and Stinebrickner (2012Stinebrickner ( , 2014) collect a panel of beliefs about own grade performance and ability from Berea College undergraduates. Stinebrickner and Stinebrickner (2012) use the data to model and analyze college dropout behavior and find that learning about own academic ability and grade performance plays a prominent role in determining observed college dropout.…”
Section: Recent Studies On Expectations For Schooling and Relatedmentioning
confidence: 99%
See 1 more Smart Citation